Management and Outcomes of Bilateral Acetabular Fractures: A Case report - Reza Zandi; Ahmadreza Ahmadi Abdashti; Nasim Nouri (Journal of Orthopedic and Spine Trauma)
Bilateral acetabular fractures are a rare type of acetabular fracture and because of a lack of information about these types of fractures, the management of bilateral acetabular fractures is challenging. We show a case of a 25-year-old young man with a bilateral acetabular fracture (left transverse fracture of the acetabulum and right posterior column fracture of the acetabulum) secondary to severe trauma following a road accident with no other pelvic damage who was treated in our department.